Bacillus Calmette-Guerin improves local and systemic response to radiotherapy in invasive bladder cancer - Prack Mc Cormick, Bárbara Patricia (2017)
BackgroundA key factor contributing to radio-resistance in conservative invasive bladder cancer (BCa) treatment is tumor hypoxia and a strategy to overcome it is to trigger the production of nitric oxide (NO). On the other hand, ionizing radiation (IR) applied to a primary tumor can induce immunogenic cell death which may set off a cytotoxic immune response against the primary tumor and its metastasis.PurposeTo study in vitro and in vivo, the role of BCG as a local sensitizer to overcome hypoxia-associated radio-resistance through the production of NO, and as an immune-stimulator to be used in combination with IR to generate a systemic response for invasive BCa treatment.Materials and methodsWe selected the invasive murine BCa cell line MB49-I which expresses inducible NO synthase and produces NO, cultured in vitro in 2D and 3D models, and inoculated in vivo in the subcutaneous of syngeneic mice.Resultsin vitro, multicellular murine invasive spheroids mimicked in vivo central tumor necrosis. BCG pre-treatment radio-sensitized spheroids through the induction of NO production, while no effect was shown in monolayers. In vivo, not only did BCG improve the local response to IR but it also decreased the metastatic spread and promoted the development of abscopal effect/rejection of a second tumor.ConclusionSince BCG has already and successfully been used for the treatment of non-invasive BCa and it improves the response to ionizing radiation in invasive BCa, these results are translational relevant to be analyzed in patients with this pathology.